The Relationship Between Glycemic Control and the Triglyceride-to-HDL Ratio as a Predictor of Cardiometabolic Risk in Patients with Type 2 Diabetes Mellitus - Prasetyaning Estu Pratiwi (Universitas Malahayati Lampung, 2025)
ABSTRACT Atherogenic dyslipidemia is one of the major risk factors for cardiometabolic complications in patients with type 2 diabetes mellitus (T2DM). The triglyceride-to-high-density lipoprotein cholesterol (TG/HDL) ratio is commonly used as an indicator of cardiometabolic risk. However, the association between the degree of glycemic control and the TG/HDL ratio remains inconsistent. To determine the association between the degree of glycemic control (HbA1c) and the TG/HDL ratio as a predictor of cardiometabolic risk in patients with T2DM. This cross-sectional study included 84 T2DM patients attending the internal medicine outpatient clinic at a hospital. Data were analyzed using Chi-square test, Spearman correlation, logistic regression, and Kruskal–Wallis test. There was no significant association between glycemic control categories and the TG/HDL ratio (p=0.702). Logistic regression analysis also revealed no significant result (p=0.703). The Spearman correlation between HbA1c and the TG/HDL ratio was not statistically significant (r = -0.062; p = 0.574). The Kruskal–Wallis test yielded a p-value of 0.890. No significant association was found between the degree of glycemic control and the TG/HDL ratio as a predictor of cardiometabolic risk in patients with T2DM. Further studies with better control of confounding variables and larger sample sizes are warranted. Keywords: Type 2 Diabetes Mellitus, Glycemic Control, Hba1c, TG/HDL Ratio, Cardiometabolic Risk, Atherogenic Dyslipidemia.